2002
DOI: 10.1007/s00223-001-1080-4
|View full text |Cite
|
Sign up to set email alerts
|

Bone-Protecting Effect of Safflower Seeds in Ovariectomized Rats

Abstract: Safflower (Carthamus tinctorius L.) seeds have long been clinically used in Korea to promote bone formation and prevent osteoporosis. However, the beneficial effect has not been scientifically evaluated. Thus, in the present study we investigated whether phytoestrogen rich safflower seeds reduce bone loss in ovariectomized rats. Female Sprague-Dawley rats were subjected to bilateral ovariectomy or sham surgery. One week after the operation, ovariectomized rats were either fed a diet containing defatted safflow… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
39
0
2

Year Published

2004
2004
2014
2014

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 80 publications
(44 citation statements)
references
References 0 publications
1
39
0
2
Order By: Relevance
“…Safflower (Carthamus tinctorius L.) seeds have long been clinically used in Korea to promote bone formation and prevent osteoporosis (97), and dietary supplementation with safflower seeds partially protected against ovariectomy-induced bone loss in rats (97). Preliminary studies indicated that this activity was associated with the polyphenolic fraction of the safflower seed, but the specific components responsible were not identified.…”
Section: Other Classes Of Phytoestrogensmentioning
confidence: 99%
“…Safflower (Carthamus tinctorius L.) seeds have long been clinically used in Korea to promote bone formation and prevent osteoporosis (97), and dietary supplementation with safflower seeds partially protected against ovariectomy-induced bone loss in rats (97). Preliminary studies indicated that this activity was associated with the polyphenolic fraction of the safflower seed, but the specific components responsible were not identified.…”
Section: Other Classes Of Phytoestrogensmentioning
confidence: 99%
“…Safflower seeds rich in unsaturated fatty acid and a-linoleic acid have been commonly consumed as vegetable oils in the USA and Europe, and also used for clinical treatments of osteoporosis and rheumatism in Korea. 9) Although the biological activities of this plant have been reported extensively, there is no documentation related to inhibitory activity with respect to melanogenesis. Thus, the present study was undertaken to investigate the melanogenesis inhibitory activity of safflower seeds and to identify further the active compounds.…”
mentioning
confidence: 99%
“…Carthami Tinctorii Fructus increased the level of serum IGF-I and lengths of femur and tibia, however, its effect was very small and transient (Lee et al, 2009). Kim et al (2002) reported that Carthami Tinctorii Fructus partially prevents ovariectomy-induced bone loss. However, the effect of individual drug was less than those of all drugs, prescription KBS.…”
Section: Discussionmentioning
confidence: 99%